2015
DOI: 10.15560/11.1.1530
|View full text |Cite
|
Sign up to set email alerts
|

The social wasp community (Hymenoptera, Vespidae) and new distribution record of Polybia ruficeps in an area of Caatinga Biome, northeastern Brazil

Abstract: Social wasps are broadly distributed in Brazil, and their distribution is closely related to local plant composition. However, only a few studies on the diversity of these insects have been carried out in northeastern Brazil, and in Caatinga Biome the diversity is probably underestimated due to the lack of inventories for the region. Aiming at advancing the knowledge about the wasp fauna, we carried out this study from October 2005 to September 2006 in Ibipeba, northeastern Brazil. We collected 172 wasps of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…These two species had been reported to Caatinga, and found in other studies realized on Northeastern Brazil states Melo et al, 2015). Andena and Carpenter (2014) registered only nine species of social wasps in Paraiba state, being the addition of those two new species a significant increase on the diversity of Polistinae.…”
Section: Social Wasps From Cariri Paraiba Brazilsupporting
confidence: 62%
See 2 more Smart Citations
“…These two species had been reported to Caatinga, and found in other studies realized on Northeastern Brazil states Melo et al, 2015). Andena and Carpenter (2014) registered only nine species of social wasps in Paraiba state, being the addition of those two new species a significant increase on the diversity of Polistinae.…”
Section: Social Wasps From Cariri Paraiba Brazilsupporting
confidence: 62%
“…Melo et al, (2015) reported these species also had the major abundance and constancy in the Caatinga, Bahia state. Other similar studies showed P. occidetalis and P. ignobilis as abundant and constant in tropical dry forests of Brazil (Aguiar & Santos …”
Section: Social Wasps From Cariri Paraiba Brazilmentioning
confidence: 95%
See 1 more Smart Citation
“…In 1978, Richards publishes the book "The Social Wasps of the Americas, Excluding the Vespinae", which comprehends an extensive review on the neotropical species, with details on their distribution, morphology and biology; this publication instantly became a milestone for posterior studies on the group, and references to it can still be found in recent publications (e.g. Melo et al, 2015;Jacques et al, 2015).…”
mentioning
confidence: 99%
“…Vespas sociais apresentam ainda grande potencial para controle de populações de outros insetos em ambientes de agrossistemas (elisei et al 2010; de souza et al 2011) além de atuarem como bioindicadoras de qualidade ambiental (urBini et al 2006;souza et al 2010). Ademais, esses insetos podem exercer importante função no transporte do pólen, fazendo parte da comunidade de polinizadores de algumas espécies vegetais (Hermes & KöHler 2006;Clemente et al 2012;somavilla & KöHler 2012;melo et al 2015).…”
Section: _____________________________________unclassified